2022
DOI: 10.3390/cancers14153825
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Co-Diagnoses in Patients with Colorectal Cancer: A Retrospective Cohort Study of 17,824 Outpatients in Germany

Abstract: Background: The prognosis of colorectal cancer (CRC) patients is determined to a decisive extent by comorbidities. On the other hand, anti-cancer treatments for CRC are associated with relevant toxicities and may therefore cause additional comorbidities. Methods: This retrospective cohort study assessed the prevalence of various diseases in patients 12 months before and 12 months after an initial diagnosis of colorectal cancer (ICD-10: C18, C20) in 1274 general practices in Germany between January 2000 and Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It has already been shown that the selection of practices included in the Disease Analyzer database is representative of general and specialist practices in Germany, and the database has served as the basis for previous studies focusing on cancer [22,24,25].…”
Section: Databasementioning
confidence: 99%
“…It has already been shown that the selection of practices included in the Disease Analyzer database is representative of general and specialist practices in Germany, and the database has served as the basis for previous studies focusing on cancer [22,24,25].…”
Section: Databasementioning
confidence: 99%
“…The panel of practices included in the Disease Analyzer database has previously been shown to be representative of office-based practices in Germany [18]. The database has been widely used for epidemiological studies in recent years, including studies on PPIs [9,19] or cancer [20,21].…”
Section: Databasementioning
confidence: 99%
“…This retrospective cohort study was based on data from the Disease Analyzer database (IQVIA). This data source has already been used in several previous studies focusing on depression and colorectal cancer [19][20][21][22], and it contains anonymous data on diagnoses, prescriptions, and basic demographic data from computer systems used in office-based practices [23]. The database contains approximately 3000 office-based practices in Germany.…”
Section: Databasementioning
confidence: 99%